Purification of Biotransformation Products of Cis-Isoflavan-4-Ol by Biphenyl Dioxygenase of Pseudomonas pseudoalcaligenes Kf707 Strain Expressed in Escherichia coli - Tri Ratna Sulistiyani; Agus Budiyanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
Isoflavone has multiple beneficial effects on human health, especially as antioxidant and anticancer. Biotransformation of two enantiomers (CE1 and CE2) of cis-isoflavan-4-ol by E. coli JM109 (pJHF108) carrying a biphenyl dioxygenase gene from P. pseudoalcaligenes KF707 produced two products and they were designated as CM1 and CM2. They had retention time at 11.9 and 14.6 min, respectively, and same absorption peaks at 204, 220 and 275 nm. CM1 and CM2 had [M-H2O+H]+ at m/z 225. Based on the molecular mass, hydrolysis products, and previous report, this study proposed that epoxidation occurred on cis-isoflavan-4-ol. Chloroform extraction was done to improve the stability of CM1 and CM2.